Optimization of dispersing agents for preparing YAG transparent ceramics - 巴学巍 李江 潘裕柏 刘婧 姜本学 刘文斌 寇华敏 郭景坤 (Journal of rare earths, 2013)
The suspensions of the powder mixture of yttria and alumina were prepared by the aqueous tape casting method. Rodia DP270, Dolapix CE64, citric acid and Dammonium 3008 were used as dispersing agents. The morphologies of the powders and the fracture surface of the green body were observed by scanning electron microscopy （SEM）. The zeta potential test was employed to characterize the surface charge states of different suspensions. The dispersion of the suspensions was analyzed by the rheological tests and the sedimentation experiments. The results indicated that the yttria and alumina powder mixtures were well dispersed by the dis- persing agents. The rheological curves showed shear thinning behavior. The most efficient dispersing agent was Dammonium 3008. The optimum usage of Dammonium 3008 was 1.0 wt.%. The green body was dense and no interface between the adjacent layers was found. The in-line transmittance of the as-sintered YAG ceramic was higher than 80% between 400 and 1100 urn.